Cell-Specific Protective Signaling Induced by the Novel AT2R-Agonist NP-6A4 on Human Endothelial and Smooth Muscle Cells - Toedebusch, Ryan; Belenchia, Anthony; Pulakat, Lakshmi (Frontiers in Pharmacology, 2018)
Cardiovascular disease incidence continues to rise and new treatment paradigms are warranted. We reported previously that activation of Angiotensin II receptor (encoded by the X-linked Agtr2 gene) by a new peptide agonist, NP-6A4, was more effective in protecting mouse cardiomyocyte HL-1 cells and human coronary artery vascular smooth muscle cells (hCAVSMCs) from acute nutrient deficiency than other drugs tested. To elucidate further the protective effects of NP-6A4 in human cells, we studied the effects of NP-6A4 treatment on functions of human coronary artery endothelial cells (hCAECs), and hCAVSMCs. In hCAVSMCs, NP-6A4 (1µM) increased Agtr2 mRNA (6-fold, p < 0.05) after 12-hr exposure, whereas in hCAECs, significant increase in Agtr2 mRNA (hCAECs: 8-fold) was observed after prolonged exposure. Interestingly, NP-6A4 treatment (1µM, 12 hr) increased AT2R protein levels in all human cells tested. Pre-treatment with AT2R-antagonist PD123319 (20µM) and anti-AT2R siRNA (1µM) suppressed this effect. Thus, NP-6A4 activates a positive feedback loop for AT2R expression and signaling in hCAVSMCs and hCAECs. NP-6A4 (1µM-20µM) increased cell index (CI) of hCAVSMCs as determined by real time cell analyzer (RTCA), indicating that high concentrations of NP-6A4 were not cytotoxic for hCAVSMCs, rather promoting better cell attachment and growth. Seahorse Extracellular Flux Assay revealed that NP-6A4 (1µM) treatment for 7 days increased whole cell-based mitochondrial parameters of hCAVSMCs, specifically maximal respiration (p < 0.05), spare respiratory capacity (p < 0.05) and ATP production (p < 0.05). NP-6A4 (1µM; 7 days) also suppressed Reactive Oxygen Species (ROS) in hCAVSMCs. Exposure to Doxorubicin (DOXO) (1µM) increased ROS in hCAVSMCs and this effect was suppressed by NP-6A4 (1µM). In hCAECs grown in complete medium, NP-6A4 (1µM) and Ang II (1µM) exerted similar changes in CI. Additionally, NP-6A4 (5µM: 12hr) increased expression of eNOS (6-fold, p < 0.05) and generation of nitric oxide (1.3-fold, p < 0.05) in hCAECs and pre-treatment with PD123319 (20µM) suppressed this effect partially (65%). Finally, NP-6A4 decreased phosphorylation of Jun-N-terminal kinase, implicated in apoptosis of ECs in atherosclerotic sites. Taken together, NP-6A4, through its ability to increase AT2R expression and signaling, exerts different cell-specific protective effects in human VSMCs and ECs.